Anti-TNF and postoperative complications in abdominal crohn's disease surgery - Yamamoto, Takayuki (2019)
Background: Biological therapy with anti-Tumour Necrosis Factor (TNF)-α agents revolutionised the treatment of inflammatory bowel disease over the last decades. However, there may be an increased risk of postoperative complications in Crohn’s disease (CD) patients treated with anti-TNF-α agents prior to abdominal surgery. Objective: To evaluate the effects of preoperative anti-TNF-α therapy on the incidence of complications after surgery. Methods: A critical assessment of the results of clinical trial outcomes and meta-analyses on the available data was conducted. Results: Based on the outcomes of previous reports including meta-analyses, preoperative use of anti-TNF-α agents modestly increased the risk of overall complications and particularly infectious complications after abdominal surgery for CD. Nevertheless, previous studies have several limitations. The majority of them were retrospective research with heterogeneous outcome measures and single centre trials with relatively small sample size. In retrospective studies, the standard protocol for assessing various types of postoperative complications was not used. The most serious limitation of the previous studies was that multiple confounding factors such as malnutrition, use of corticosteroids, and preoperative sepsis were not taken into consideration. Conclusion: Among patients treated with preoperative anti-TNF-α therapy, the risk of overall complications and infectious complications may slightly increase after abdominal surgery for CD. Nevertheless, the previous reports reviewed in this study suffered from limitations. To rigorously evaluate the risk of anti-TNF-α therapy prior to surgery, large prospective studies with standardised criteria for assessing surgical complications and with proper adjustment for confounding variables are warranted.